Laparoscopic Techniques: What is the Role in Inflammatory Bowel Disease? - Tracy L Hull (Canadian Journal of Gastroenterology)
Laparoscopic cholecystectomy has quickly become the preferred technique for removing the gallbladder. Real advantages in the area of laparoscopic gallbladder removal have spurred interest towards other areas of laparoscopic surgery. There has been interest in laparoscopic bowel surgery but this approach has not gained popularity as quickly as gallbladder surgery. Reasons surround the fact that the bowel is a continuous organ (versus an end organ like the gallbladder) laden with bacteria and it has a rich blood supply. These differences make laparoscopic bowel surgery more difficult and challenging. If inflammatory bowel disease (IBD) is considered, the indications to approach surgery laparoscopically fall into two categories: current and future indications. The current indications are diagnostic laparoscopy, fecal diversion, limited bowel resections with extracorporeal anastomosis and stoma closures. Future indications include laparoscopic subtotal colectomy and laparoscopic assisted pelvic pouch procedures. As experience is gained and laparoscopic instruments are modified and refined for bowel surgery, intracorporeal anastomosis and more extensive bowel resections will be feasible. Currently laparoscopic bowel surgery can be done in select circumstances for problems associated with IBD. It has yet to be proven if doing the surgery laparoscopically provides advantages for bowel surgery as has been demonstrated with gallbladder surgery. Prospective studies are underway to answer these questions.